2014
DOI: 10.1111/opo.12164
|View full text |Cite
|
Sign up to set email alerts
|

Refractive errors in a Brazilian population: age and sex distribution

Abstract: Astigmatism was the most prevalent refractive error in a Brazilian population. There was a strong relationship between age and all refractive errors and between hyperopia and sex. WTR astigmatism was more frequently associated with hyperopia and ATR astigmatism with myopia. The vast majority of participants had low-grade refractive error, which favours planning aimed at correction of refractive error in the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 24 publications
5
24
1
Order By: Relevance
“…Numerous studies across the world have reported the prevalence of refractive errors as an index of descriptive epidemiology, and it may be the only field in refractive errors which includes reports from almost every corner of the world. 2 , 3 , 4 , 8 , 12 , 14 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 73 , 74 , 75 , 76 , 78 , 79 , 80 , 81 , 82 , 83 ,…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies across the world have reported the prevalence of refractive errors as an index of descriptive epidemiology, and it may be the only field in refractive errors which includes reports from almost every corner of the world. 2 , 3 , 4 , 8 , 12 , 14 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 73 , 74 , 75 , 76 , 78 , 79 , 80 , 81 , 82 , 83 ,…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the prevalence of different types of refractive errors in the representative age group or in general population have not been studied/discussed. A review of literature reveals different minimum/maximum cut-off values to define the refractive errors [ 7 , 10 , 17 , 21 , 32 , 33 ] and data analysis methods (patient wise versus eye wise distribution) [ 7 , 13 , 30 , 34 , 35 ] etc . These differences will be highlighted while comparing the current study results with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that a myopic shift usually starts earlier in life, and myopic patients start to wear spectacles at a younger age compared with hyperopic patients. 20 , 21 Therefore, myopic individuals would benefit from earlier UV protection than hyperopic or emmetropic individuals. Almost all spectacle lenses prescribed in South Korea can reduce UV exposure in varying degrees, although the extent of UV blockage can fall short of United States Food and Drug Administration recommendations.…”
Section: Discussionmentioning
confidence: 99%